Diagnostic reliability and accuracy of the hydraulic contrast lift protocol in the radiographic detection of sinus lift and perforation: ex vivo randomized split-mouth study in an ovine model - Mohamed A. Youssef; Nadine von Krockow; Jacqueline A. Pfaff (Nature Publishing Group, 2024)
Abstract Objectives Assessing the diagnostic reliability, validity, and accuracy of the hydraulic contrast lift protocol during transcrestal sinus floor elevation in detecting the lift and perforation of the sinus membrane before graft material application and assessing the effect of its use on the operator's diagnostic confidence. Material and methods A single-blind randomized split-mouth study on fresh refrigerated sheep heads. The first intervention consisted of injecting 0.5 ml iodinated contrast medium on the test side and 0.5 ml saline on the control side. In the second intervention artificial sinus membrane perforations were created followed by injecting 0.5 ml iodinated contrast medium on the test side and 0.5 ml saline on the control side. Intraoperative periapical radiographs were taken for both interventions. The resulting 40 radiographs were assessed by 10 examiners to provide interpretations and confidence ratings. The primary endpoints were diagnostic reliability, validity, accuracy, and perceived diagnostic confidence. Results In the hydraulic contrast lift protocol, the detection rate was 99% for sinus elevations and 98% for perforations, the saline protocol yielded a detection rate of 28% and 20% respectively. The hydraulic contrast lift protocol demonstrated a high level of inter-rater agreement for the diagnosis of elevations (p < 0.001) and perforations (p < 0.001), strong diagnostic validity for the diagnosis of elevations (p < 0.001) and perforations (p < 0.001), high sensitivity and specificity (p < 0.001) and higher mean diagnostic confidence ratings for both interventions when compared to the saline protocol (p < 0.001). The difference between the predicted probability for correct diagnosis of the hydraulic contrast lift protocol and the saline protocol was significant (p < 0.001) for the detection of both elevations and perforations. Conclusion Following the hydraulic contrast lift protocol, the use of a radiographic contrast medium can reliably confirm sinus membrane lift and detect perforation during transcrestal sinus floor elevation prior to bone graft application in addition to improving the diagnostic confidence of the operator while relying on periapical radiographs.